2022
DOI: 10.1186/s13071-022-05274-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis on transcriptomics of ivermectin resistant and susceptible strains of Haemonchus contortus

Abstract: Background Ivermectin (IVM) is one of the most important and widely used anthelmintics in veterinary medicine. However, its efficacy is increasingly compromised by widespread resistance, and the exact mechanism of IVM resistance remains unclear for most parasitic nematodes, including Haemonchus contortus, a blood-sucking parasitic nematode of small ruminants. Methods In this study, an H. contortus IVM-resistant strain from Zhaosu, Xinjiang, China, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Finally, the CC terms displayed the presence of intracellular structures and an intracellular membrane-bounded organelle (GO:0043231) and were also integral components of the cell membrane (GO:0016020, 0016021). These terms play important roles in the parasite development and in the metabolism of anthelmintic drugs [ 50 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the CC terms displayed the presence of intracellular structures and an intracellular membrane-bounded organelle (GO:0043231) and were also integral components of the cell membrane (GO:0016020, 0016021). These terms play important roles in the parasite development and in the metabolism of anthelmintic drugs [ 50 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other important genes, such as those associated with the serine protease family (GO:0008236, GO:0004177), appear to be important as potential vaccine candidates, as has been notified from the nematode Brugia malayi (i.e., Bm-ALT and Bm-VAL-1) [ 63 ]. With these examples, a database of novel transcriptomes could expand our knowledge about nematode biology through the functional annotation of genes and could be directed to obtain future vaccines, molecular targets for competitive studies to inhibit AR receptors and molecular markers for AR diagnosis [ 23 , 50 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, farmers generally used single anthelmintic drugs for their adult animals; some roundworm populations may develop genetic mutations that allow them to resist the effects of these drugs. When this happens, the roundworms are said to be "resistant" to the drugs (Gilleard, 2013;Tuersong et al, 2022). The study of Paraud et al (2016) has similarly shown that when roundworms develop resistance to ivermectin, they may also become resistant to other ML drugs, such as moxidectin.…”
mentioning
confidence: 99%